A Stiff Extracellular Matrix Favors the Mechanical Cell Competition that Leads to Extrusion of Bacterially-Infected Epithelial Cells - Aparicio-Yuste, Raúl; Muenkel, Marie; Clark, Andrew G.; Gómez-Benito, María J.; Bastounis, Effie E. (Frontiers in Cell and Developmental Biology, 2022)
Cell competition refers to the mechanism whereby less fit cells (“losers”) are sensed and eliminated by more fit, neighbouring cells (“winners”), and arises during many processes including intracellular bacterial infection. Extracellular matrix stiffness (ECM) can regulate important cellular functions, such as motility, by modulating the physical forces that cells transduce and could thus modulate the output of cellular competitions. Herein, we employ a computational model to investigate the previously overlooked role of ECM stiffness in modulating the forceful extrusion of “loser” infected cells by “winner” uninfected cells. We find that increasing ECM stiffness promotes the collective squeezing and subsequent extrusion of infected cells due to differential cell displacements and cellular force generation. Moreover, we discover that an increase in the relative cell stiffness between infected and surrounding uninfected cells as well as a smaller infection focus size, both promote squeezing of infected cells, and this phenomenon is more prominent on stiffer compared to softer matrices. Our experimental findings validate the computational predictions by demonstrating increased collective cell extrusion on stiff matrices and glass as opposed to softer matrices, leading to decreased bacterial spread in the basal cell monolayer in vitro. Collectively, our results suggest that ECM stiffness plays a major role in modulating the competition between infected and uninfected cells, with stiffer matrices promoting this battle through differential modulation of cell mechanics between the two cell populations.